Thematic Study: The Role Of Educators In The Prophet's Hadith - Febby Adinda; Nur Haliza Palem; Nur Haflisma Lubis; Burhanuddin, Burhanuddin; Zulfahmi Lubis (Sean Institute, 2025)
Hadith of the Prophet Muhammad sallallaahu ' Alaihi Wasallam . In this case this , the author will also to expose about Takhrij Hadith which includes criticism narrator and narrator , explanation hadith , its application and also its conclusion . The role of educators is very important and interesting thing For discussed . Because , without knowing how should role educator a educator No will Can to fulfill his obligation with maximum . This paper written with use method qualitative with approach Library study . With method researcher analyze related data​​ with hadith hadith of the Prophet Muhammad sallallaahu ' alaihi Wassallam . With do analysis said , researchers find meaning How role a educators contained in the hadith of the Prophet Muhammad Shallahu ' Alaihi Wassallam . With This writer get formulation that role educators who exist in hadith of the Prophet Muhammad sallallaahu ' Alaihi Peace be upon you is that teacher​ is a knowledgeable person so must respected , teachers must also own characteristic responsible answer and the teacher must sincere teach science for science That No stop on him However become inheritance for his students.